THE PREFERENCES OF CHOOSING TAXI-HAILING MODE ATTRIBUTES THROUGH THE BWS-CASE 1 - Mohsen MAKAREMI-SHARIFI; Amir Abbas RASSAFI (Scientific Journal of Silesian University of Technology. Series Transport)
With the widespread use of the Internet in everyday life, new businesses have emerged, causing significant changes in the market, while some traditional businesses were marginalized. One of the emerging businesses is taxi-hailing, which has gained popularity among the public. This study examines ten attributes of taxi-hailing and asks individuals about their preferences for these attributes through a questionnaire. Unlike the traditional approach of dealing with discrete choice models, which focuses on choosing the best (most important) alternative only, the role of the worst (least important) alternative is also considered in this type of modelling. The present study utilizes case 1 (out of the three available cases) of this scaling method, called “best-worst”, which focuses on attributes. Each questionnaire includes 12 questions about taxi-hailing attributes, where respondents have to state their preference in selecting the best and the worst ones. The results indicate that security and reassurance are the most crucial attributes when deciding this transportation mode, followed by accessibility. Compliance with health issues and social distancing ranked as the least significant attribute.